Simulation and Evaluation of Hydro-processing for Jet Fuel Quality Improvement Using Aspen HYSYS: A Case Study (المجلة الدولية للبحوث العلمية, 2026)
This study focuses on improving jet fuel quality by removing sulfur compounds, represented by the Thiophene compound, and enhancing its physical and chemical properties using thermal treatment, based on simulation. The Plug Flow Reactor (PFR) was operated at 400 °C and 2500 kPa to treat the feedstock, targeting the removal of Thiophene as the primary sulfur compound. The sulfur content decreased from 7.0 xi in the initial mixture (Feed-Stream) to approximately 0.0085 xi in the product stream (Treated-Feed) after treatment by HDS-Reactor, this achieves a removal efficiency of approximately 98.79%. After the reactor, the three-phase separation unit was operated at a temperature of 145.3 °C and a pressure of 897.7 kPa, where it successfully transferred most of the H₂S (0.0716 xi) produced by the desulfurization process to the gas phase, reducing its concentration in the liquid hydrocarbon phase (Final-Product) to about 0.0080 xi , which greatly reduced the solubility of acid gases in the final product. On the other hand, a mixing unit was also applied to add performance-enhancing materials, namely C2=GC4EthrAc and 1-Dodecanol. These additions contributed to improving density, viscosity, and freezing point without affecting the basic hydrocarbon structure. The final analysis results showed that most of the properties met the requirements of ASTM D1655 specifications for jet fuel, with a density of 740.5 kg/m³, a viscosity reduced to 0.56 cP, and the fuel's low heat value (LHV) was approximately 43,640 kJ/kg, while its high heat value (HHV) was approximately 46,464 kJ/kg. Therefore, these results show an effective methodology for producing high-quality jet fuel the process to meet international specifications.